Business Process Outsourcing For Kubang Pasu Land Office - Faridah, Ismail (2004)
Many organizations are increasingly outsourcing their back-office operations through IT applications. This scenario due to number of reasons leading by the cost reduction, shortened time-to-time, lack of internal expertise and risk reduction. However, the adoptions of back-office model are still new for many organizations. Only a few organizations have formal approach to make back-office outsourcing decision. In Malaysia context, many governmental organizations nowadays are moving towards e-government to improve their services and business through IT outsourcing. Outsourcing is a dynamic process in the sense that the related decisions and actions must continuously to changes in strategic direction of the organization. This work reveals on the problem facing by each units at Kubang Pasu Land Office due to the five thousand backlog files. At the meantime, this work also determining the potential back-office process that can be outsourcing in order to give effective and efficient services to citizen.